2016
DOI: 10.18632/oncotarget.12832
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor microRNA signature predicts recurrence and survival in patients with locally advanced esophageal adenocarcinoma

Abstract: Esophageal adenocarcinoma (EAC) is an aggressive cancer necessitating the development of improved risk stratification tools for personalized care. Previously, microRNAs have been shown to correlate with the progression and prognosis of various cancer types; however, the value in EAC remains largely unexplored. We performed global microRNA profiling on 32 formalin-fixed, paraffin-embedded EAC specimens to identify microRNAs associated with progression. Literature search and pathway analysis further refined outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Several studies have demonstrated that miR-96-5p is overexpressed in various cancers, including colorectal cancer [13], pancreatic carcinoma [14], prostate cancer [15], hepatocellular carcinoma [16], and breast cancer [17], and it is oncogene that promotes cell proliferation. It has been reported that miR-652-5p is associated with non-small cell lung cancer [18], esophageal adenocarcinoma [19], and breast cancer [20], while the mechanism of miR-652-5p was not elaborated. Current research on miR-222-5p has focused on the role of angiogenesis in the endothelium [21,22], and few studies investigated the effect of miR-222-5p in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that miR-96-5p is overexpressed in various cancers, including colorectal cancer [13], pancreatic carcinoma [14], prostate cancer [15], hepatocellular carcinoma [16], and breast cancer [17], and it is oncogene that promotes cell proliferation. It has been reported that miR-652-5p is associated with non-small cell lung cancer [18], esophageal adenocarcinoma [19], and breast cancer [20], while the mechanism of miR-652-5p was not elaborated. Current research on miR-222-5p has focused on the role of angiogenesis in the endothelium [21,22], and few studies investigated the effect of miR-222-5p in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that aberrant expression of miRs, such as miR‐21, miR‐let‐7 and miR‐24, is associated with proliferation, apoptosis, and invasion of CRC cells by targeting corresponding function proteins . As for miR‐219‐5p, it has been reported as a tumor suppressor in gastric cancer, glioblastoma and esophageal adenocarcinoma, and it also works as a negative regulator of cell proliferation in CRC by targeting platelet‐derived growth factor receptor . However, the mechanism between miR‐219‐5p and metastasis of CRC remains unclear.…”
mentioning
confidence: 99%
“…(4) Several studies have indicated that aberrant expression of miRs, such as miR-21, miR-let-7 and miR-24, is associated with proliferation, apoptosis, and invasion of CRC cells by targeting corresponding function proteins. (5) As for miR-219-5p, it has been reported as a tumor suppressor in gastric cancer, glioblastoma and esophageal adenocarcinoma, (6)(7)(8) and it also works as a negative regulator of cell proliferation in CRC by targeting platelet-derived growth factor receptor. (9) However, the mechanism between miR-219-5p and metastasis of CRC remains unclear.LEF1, a member of the high mobility group protein family, can activate the transcription of Wnt target genes, such as c-myc, cyclin D1, MMP-1 and MMP-7, by combing with b-catenin and forming the b-catenin/TCF/LEF complex, to regulate cell behavior.…”
mentioning
confidence: 99%
“…Among miRNA downregulated upon BORIS KD, miR-7-2-3p and let-7a-5p stand out with highest fold ( Supplementary Table S4 ). miR-7-2-3p information is presently limited to biomarker surveys [ 91 , 92 ]. The let-7a-5p expression is normally maintained at a relatively stable level [ 93 ], and the three loci that encode it have no direct association with BORIS binding in K562.…”
Section: Resultsmentioning
confidence: 99%